2011
DOI: 10.2478/v10089-011-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Population and Economy in Śląskie Voivodship in the Context of the Suburbanization Process

Abstract: ABSTRACT. This paper attempts to determine and describe suburbanization stages (especially in the context of political-economic transformations and population changes) and also, to verify classical models of urbanization stages as a system of concentric zones, basing on historical process of development of complex settlement systems of Katowice voivodship (according to the former administrative division), i.e., Katowice conurbation, Rybnik agglomeration, Bielsko-Biała agglomeration, and Częstochowa agglomerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 1 publication
0
6
0
5
Order By: Relevance
“…international emigration and migration to other urban centres of Poland (KRZYSZTOFIK SITEK ET AL., 2013). RUNGE & KŁOSOWSKI (2011) researched the dynamics of the population and migration processes in urban agglomerations of the Silesian voivodeship for the years 1978-2008. These studies showed that, in terms of the core -the suburban zone of the agglomeration, the suburbanisation process in the Katowice conurbation was virtually unnoticeable.…”
Section: Discussionmentioning
confidence: 99%
“…international emigration and migration to other urban centres of Poland (KRZYSZTOFIK SITEK ET AL., 2013). RUNGE & KŁOSOWSKI (2011) researched the dynamics of the population and migration processes in urban agglomerations of the Silesian voivodeship for the years 1978-2008. These studies showed that, in terms of the core -the suburban zone of the agglomeration, the suburbanisation process in the Katowice conurbation was virtually unnoticeable.…”
Section: Discussionmentioning
confidence: 99%
“…Examining suburban areas of big cities, as well as metropolitan areas in Poland, researchers point to the fact that since 1999 the population of rural municipalities has been increasing, predominantly due to a positive migration balance, whereas the inflow of population to rural areas has a permanent increasing tendency [19], [20], [25]. Analysing building permits issued in the examined 8 municipalities, one may come to a conclusion that in the period of 2003 -2017 the examined area experienced the construction of 5,030 new buildings, which indicates the intense development of residential housing (predominantly one-family settlements) which is related to the dynamic increase of population in suburban areas [8], [16], [17], [29], [10]. Newly constructed residential settlements are predominantly erected by private persons, as well as developers.…”
Section: Usage Of Land In Suburban Area Of Katowice Conurbationmentioning
confidence: 99%
“…Analiza procesów urbanizacji w obrębie konurbacji katowickiej wskazuje na wyraźne odmienności w tym zakresie w stosunku do innych układów osadniczych (Runge, Kłosowski 2011). Widoczne są także różnice w obrębie samej konurbacji katowickiej (wewnątrzregionalne) w zakresie kształtowania się owych procesów (Runge, Kłosowski 2011). Do połowy XVIII w. ośrodkami aktywności społeczno-gospodarczej były dzisiejsze obrzeża konurbacji katowickiej (Tarnowskie Góry, Toszek, Pyskowice, Mikołów, Czeladź, Będzin, Pszczyna).…”
Section: Procesy Suburbanizacjiunclassified